2016
DOI: 10.1183/13993003.00510-2016
|View full text |Cite
|
Sign up to set email alerts
|

First evaluation of QuantiFERON-TB Gold Plus performance in contact screening

Abstract: Identifying latently infected individuals is crucial for the elimination of tuberculosis (TB). We evaluated for the first time the performance of a new type of interferon-γ release assay, QuantiFERON-TB Plus (QFT-Plus), which includes an additional antigen tube (TB2), stimulating both CD4 and CD8 T-cells in contacts of TB patients.Contacts were screened for latent TB infection by tuberculin skin test, QFT-Plus and QuantiFERON-TB Gold in Tube (QFT-GIT).In 119 TB contacts, the overall agreement between QFT-Plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 32 publications
3
87
0
1
Order By: Relevance
“…We expect that the new generation of the QFT-IT test, QuantiFERON-TB Plus, could better define response to M. tuberculosis infection, by also detecting specific CD8 ϩ T cell response through the presence of an additional M. tuberculosis antigen tube. Recent studies have reported higher M. tuberculosis-specific CD8 ϩ T cell responses in patients with active TB disease compared to those with LTBI (42,43), with recent M. tuberculosis exposure (44,45) and with more severe disease (46,47). Previously, higher M. tuberculosis-specific CD8 ϩ T cell responses were observed in young children with TB (48), but no studies on QFT Plus performance in children have been performed to date.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the new generation of the QFT-IT test, QuantiFERON-TB Plus, could better define response to M. tuberculosis infection, by also detecting specific CD8 ϩ T cell response through the presence of an additional M. tuberculosis antigen tube. Recent studies have reported higher M. tuberculosis-specific CD8 ϩ T cell responses in patients with active TB disease compared to those with LTBI (42,43), with recent M. tuberculosis exposure (44,45) and with more severe disease (46,47). Previously, higher M. tuberculosis-specific CD8 ϩ T cell responses were observed in young children with TB (48), but no studies on QFT Plus performance in children have been performed to date.…”
Section: Discussionmentioning
confidence: 99%
“…The new CD8+ -specific peptides have been added to increase the sensitivity of the test because it has been shown that Mtb-specific CD8+ T-cells are mainly associated to active TB [44,45,46,47]. The first data on the performance of QuantiFERON TB Plus were reported recently [48,49,50]. When compared with the previous test version of QFT-GIT [50], equal sensitivity of the new generation QFT-plus was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The QuantiFERON-TB Gold Plus assay incorporates new antigens designed to increase test sensitivity among immunocompromised groups, including people living with HIV. The initial independent evaluations, however, have shown this new test to have minimal increased sensitivity (34). Variations of the IGRA test that utilize alternate immune readouts in response to TB antigen stimulation are also being explored.…”
Section: New Ltbi Diagnosticsmentioning
confidence: 99%